Assessment of the awareness, preparedness, and challenges of the adoption of single-use plastic reduction ordinance towards a sustainable food and beverage Micro and Small Enterprises (MSEs) in Tacloban City - Chu, Kim Trisha G.; Labrague, Maxinne C.; Lozada, Ma. Wella T.; Marquez, Khryzha Mae Joy M.; Rodriguez, Lexa Marie V.
Growing concerns over plastic waste have intensified in Tacloban City, generating around 120 tons of waste daily, including 13.2 tons of single-use plastics (Gabieta, 2024). Using a mixed-methods correlational approach, the study combined quantitative surveys and qualitative interviews with MSE owners and managers. The quantitative study gathered data from 109 respondents through questionnaires, while the qualitative study involved in-depth interviews with 11 participants. The study found that MSE owners had moderate to high awareness of the environmental problem; however, preparedness levels were mixed, and no significant relationship was found between awareness and preparedness. This indicated external challenges that hindered them from adopting sustainable practices despite their awareness of the problem. The qualitative findings revealed major challenges such as high costs, limited alternatives, a lack of local sourcing options, inconsistent enforcement of the ordinance, and client pushback. The researchers provided recommendations for enhancing compliance with the ordinance, such as increased government support, incentivized and sustainable alternatives for customers, a ban on single-use plastic packaging and utensils, and strengthened public awareness campaigns.